Immunohistochemical subtypes of the breast cancer in the ultrasound and clinical aspect – literature review - Dobruch-Sobczak Katarzyna; Gumowska Magdalena; Mączewska Joanna; Kolasińska-Ćwikła Agnieszka; Guzik Paweł (Journal of Ultrasonography, 2022)
Breast cancer is a heterogeneous disease both in its clinical and radiological manifestations and response to treatment. This is largely due to the polymorphism of the histological types as well as diversified molecular profiles of individual breast cancer types. Progress in the understanding of the biology of breast cancer was made with the introduction of immunohistochemical research into the common practice. On this basis, four main breast cancer subtypes were distinguished: luminal A, luminal B, HER2 positive (human epidermal growth factor receptor-2 positive), and triple negative cancer. The classification of a tumour to an appropriate subtype allows for the optimisation of treatment (surgery or pre-operative chemotherapy). In this study, the authors present different patterns of breast cancer subtypes in ultrasound examination and differences in their treatment, with particular emphasis on aggressive breast cancer subtypes, such as triple negative or HER2 positive. They can, unlike the luminal subtypes, create diagnostic problems. Based on multifactorial analysis of the ultrasound image, with the assessment of lesion margins, orientation, shape, echogenicity, vascularity, the presence of calcifications or assessment by sonoelastography, it is possible to initially differentiate individual subtypes.